Kynurenine enhances aryl hydrocarbon receptor signaling and expression levels of multidrug resistance genes in head and neck squamous cell carcinoma cell lines but does not change the potency of antineoplastic drugs - Bajraktari-Sylejmani, Gzona; Piribauer, Marlene; Größl, Sven; Bernhard, Patrick; Dyckhoff, Gerhard; Warta, Rolf; Herold-Mende, Christel; Theile, Dirk; Weiß, Johanna (Toxicology and applied pharmacology, 2025)
Efficacy of the standard cytotoxic drugs against head and neck squamous cell carcinoma (HNSCC) is limited, underlining the potential relevance of multidrug resistance (MDR), mediated by drug transporters and drug-metabolising enzymes. While the major regulator of these proteins, the pregnane-X-receptor, is of minor relevance for HNSCC, little is known about the aryl hydrocarbon receptor (AhR) signaling, its transcriptional effect on MDR genes and phenotypic MDR upon activation. Using established HNSCC cell lines, AhR reporter gene assays, quantitative reverse transcription polymerase chain reaction, and proliferation assays, this study demonstrates that AhR and its major cofactors (heat shock protein 90, AhR nuclear translocator, and AhR-interacting protein 1) are expressed and that AhR is active, and druggable. The potent AhR ligand, 2,3,7,8-tetrachlordibenzo-p-dioxin (TCDD) increased AhR activity in these cells up to 5.4-fold and strongly induced mRNA expression of cytochrome P450 (CYP) 1A1 (up to 224-fold) and CYP1B1 (up to 20-fold), while breast cancer resistance protein (ABCG2) was hardly enhanced (up to 2.2-fold). The endogenous ligand of AhR kynurenine (2-4-fold) and its “activated” condensation product (2-250-fold) also enhanced these genes' expression levels. However, AhR activation and target gene induction were not accompanied by relevant alterations of the antiproliferative effects of docetaxel, paclitaxel, cisplatin, carboplatin, or 5-fluorouracil. Together, this data shows that AhR signaling is in fact active in HNSCC, but its therapeutic role in HNSCC is unlikely related to induction of MDR genes. In contrast, the immune system-regulating effects of kynurenine-mediated AhR activation is likely of higher relevance and thus needs further evaluation.